Associations of Atopobium, Garderella, Megasphaera, Prevotella, Sneathia, and Streptococcus with human papillomavirus infection, cervical intraepithelial neoplasia, and cancer: a systematic review and meta-analysis - Yan Peng; Qin Tang; Shiming Wu; Chengzhi Zhao (BMC Infectious Diseases)
Abstract Background Lactobacillus spp. depleted and high diversity of vaginal microbiota is closely related to human papillomavirus infection and cervical cancer. However, the role of other microbial communities in human papillomavirus infection and cervical cancer is still unclear. Objective This study aims to systematically review the existing literature and perform a meta-analysis to statistically evaluate the relationship between vaginal microbiota, human papillomavirus infection, cervical intraepithelial neoplasia, and cervical cancer at the genus level. Methods A comprehensive search of PubMed, Web of Science, and Embase databases was conducted to identify relevant studies. We synthesized data on the relative abundance of specific bacterial species associated with human papillomavirus status and cervical lesions. SPSS 25.0 was used to compare relative abundance among multiple groups. Results The meta-analysis included 17 observational studies published between 2019 and 2023, involving 2014 participants from Asia, North America, and Africa. We found that specific vaginal microorganisms, such as Gardnerella, Prevotella, Sneathia, and Streptococcus, showed increased relative abundance with the severity of cervical lesions in human papillomavirus-negative, human papillomavirus-positive, cervical intraepithelial neoplasia, and cervical cancer patients. However, no statistically significant differences were found in that regard. Notably, Prevotella was significantly more abundant in cervical cancer patients compared to human papillomavirus-negative individuals. Sneathia was also found to be more abundant in cervical intraepithelial neoplasia and cervical cancer patients. Conclusions The specific vaginal microbial species are associated with human papillomavirus infection status and the severity of cervical lesions that may have significant implications for the prevention and treatment strategies of cervical cancer.